Strengthening Academic Integrity in Online Learning through Moral Values and Spiritual Motivation among University Students - Chaira Saidah Yusrie; Amie Primarni; Makmudi Makmudi; Agus Suryana; Nabila Yusof; Yusi Srihartini (International Journal of Educational Narratives, 2026)
Background. Ethical decision-making in online learning has emerged as a critical challenge in higher education. The shift to digital environments has inadvertently created greater opportunities for academic misconduct while simultaneously reducing direct supervision. Purpose. This study aims to analyze the influence of moral values and spiritual motivation on students’ ethical decision-making processes. Furthermore, it seeks to explore how these two internal drivers guide student responses when encountering ethical dilemmas within digital learning environments. Method. The research employed an explanatory sequential mixed-methods design. Quantitative data were gathered from 95 university students using validated Likert-scale questionnaires and processed through multiple regression analysis. To deepen the insights, qualitative data were collected from students’ written narrative responses and examined using thematic analysis. Results. The findings indicate that both moral values and spiritual motivation significantly impact ethical decision-making in online learning, with spiritual motivation identified as the stronger predictor. Conclusion. By focusing on these internal motivators, higher education institutions can more effectively strengthen academic integrity and foster a culture of ethical responsibility among university students in the digital age.